Adherence to antiretroviral therapy and factors affecting adherence among paediatric HIV patients - Govind, Kendre; Yashwant, Gabhale; Nikita, Shah; Vishal, Jadhav; Kunal, Nath; Mamta, Manglani (International Journal of Contemporary Pediatrics, 2017)
Background: Adherence to antiretroviral therapy (ART) is the strongest indicator of successful treatment of Human Immunodeficiency Virus (HIV) among children. The main aim of the present study was to know the prevalence of adherence at our centre and various factors affecting the adherence in children. Methods: It was an observational study done in children less than 15 years of age, affected with HIV. 78 children attending Paediatric Centre of Excellence (PCOE) for HIV L.T.M.G. Hospital, Sion, Mumbai were included in study, Study period was 18 months from January 2012 to June 2013. Complete history of the patients was noted in a pre-designed proforma. Baseline investigations related to HIV were done in all children. Fixed dose combination ART was started in children who fulfilled clinical and/or immunological criteria as per the NACO guidelines. Adherence was estimated using Pill count method..All the data were analysed by using 10.0 version of statistical software SPSS. Results: In this study, male children (57.7%) out numbered the females (42.3%). Majority of study subjects were more than 10 years of age. Overall adherence among subjects was 82.1% at the end of one year and non-adherence was 17.9%. There was no significant association of age and gender of the patients with adherence (p>0.05). Education, employment and knowledge towards medication of care takers was significantly associated with adherence of ART (p<0.05). Adherence of study cases had not showed any significant association with ART treatment regimen (p=0.99). At the end of one year, the mean CD4 count was significantly more as compared to baseline among adherence group and the mean CD4 count was significantly less as compared to baseline among non-adherence group. The most common reason for missed dosage was forgot to take medicine in 29 subjects (37.1 %).. Conclusion: Adherence level in this study was good. Forgot to take the medicine was the main reason given by the patients for non-adherence. Education, employment and knowledge towards medication of care takers was significantly associated with adherence of ART .But further studies are needed to explore various other factors related to adherence in children.